Application of said-ball curve with continuity in Jawi design - Nur Aliah Izzati Rosman (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2017)
The objectives of this study involved three main stages ; to detect corner points ; to determine control points ; to fit Said-Ball Curve that satisfies Continuity of Degree 1 in designing Jawi.